Community Characteristics as the Basis of Empowerment Strategies In Sustainable Environmental Hygiene Management - Andi Agustang; Hairuddin K; Andi Dody May Putra Agustang; Dian Meiliani Yulis (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
The community is one of the waste producers, so community empowerment in environmental hygiene programs is very strategic. The purpose of the study was to determine the characteristics (level of education, employment, income, a distance of the house to the TPS and TPA), and community perceptions related to sustainable environmental hygiene programs, especially towards the waste management of the city of Makassar. The data collection method used in the characteristics of society towards environmental cleanliness is carried out using a survey approach. Data analysis using qualitative and quantitative techniques. The results showed that the variety of these characteristics contributed (except the level of education) to the sustainable environmental hygiene management program. The results of Fisher's contingency coefficient test, showed a significant relationship between community characteristics, except for the level of education and sustainable environmental hygiene management programs.